PENGARUH KADAR ABU TERBANG SEBAGAI PENGGANTI SEJUMLAH SEMEN PADA BETON ALIR MUTU TINGGI - Surya Sebayang (UNIVERSITAS LAMPUNG, 2010)
Flowing concrete flow under it own weight and maintain homogeneity while filling and passingaround congested reinforcement. Flowing concrete is used to reduce or eliminate the need forvibration to reduce construction cost and reducing construction time. High strength flowingconcrete in this research used fly ash obtained from PLTU Suralaya Banten as substitutionmaterial the amount of cement. The properties investigated are workability, concrete setting time,unit weight, and compression strength. Proportion of material for concrete determined accordingto ACI 211-4R-1993 and combine with Hashimoto method. The substitution of fly ash to theconcrete are 0 %, 3%, 6%, 9%, 12% and 15% of the cement content. The test result indicated thateffect of fly ash in fresh concrete was increased the workability of the concrete. Addition of fly ashwas made fresh concrete enough cohesiveness without causing segregation. Addition of fly ashwas increased the initial and final setting time. The cylinder compression strength of fly ashflowing concrete at 7days, 14 days and 28 days was lower than compression strength of flowingconcrete without fly as at the same days. The optimum strength of fly ash flowing concrete was48,607 MPa at 56 days age in 9 % presence of fly ash.